Application of Guidance for Reading the Qur'an for Grade IV Students of MIS Muslimat NU Palangka Raya City - Desi Lestari; Ali Iskandar Zulkarnain; Muhammad Syabrina (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This study aims to find out the application of guidance for reading the Qur'an for fourth grade students of MIS Muslimat NU Palangka Raya City. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the guidance program is carried out systematically through madrasah support, individual mentoring, and the application of the Iqra method as basic learning and the Tilawati method to improve the fluency and accuracy of reading. The findings of the study revealed that some students still have difficulty in recognizing and reciting hijayah letters, especially in distinguishing between long and short readings (mad and qashr), which are influenced by differences in students' learning ability, comprehension, and focus level. To overcome these obstacles, teachers apply strategies in the form of special attention, practice and repetition of reading, effective time management, and motivation so that students are more concentrated and confident. The results of the study confirm that intensive, gradual, and continuous guidance is effective in supporting the improvement of students' Qur'an reading skills.